The association between fever in the first year of life and atopy in children with or without family history of atopic disease - Susy P. Wihadi; Budi Setiabudiawan; Cissy B. Kartasasmita (Paediatrica Indonesiana, 2007)
Background The role of repeated infection in early life in thedevelopment of childhood atopy is still controversy. Fever in thefirst year of life which is frequently associated with infections mightdecrease atopy.Objective The aim of this study was to investigate the associationbetween fever in the first year of life and atopy in children.Methods This was an observational clinical epidemiology studyperformed at Puskesmas Garuda, Padasuka, and Babakan Sari,Bandung, from January to March 2006. From 749 children, werandomly chose 150 subjects each from group with and withoutfamily history of atopic disease. Skin prick test and measurementof total serum immunoglobulin (Ig) E were performed on eachchildren. Atopy was defined as the skin prick test result waspositive to >1 allergen. The number of fever episodes in the firstyear of life was based on parents report. The relationship betweenfever and atopy was analyzed using Mantel Haenszel.Results From 284 subjects, atopy was found in 28.2% of children,of which 32.4% with and 23.9% without a family history of atopicdisease. Generally there was no significant association betweenfever and atopy. There was only decreased odds ratio withincreased fever episodes and trend analysis showed this decreasewas significant (P=0.01). The significant association betweenfever and atopy were found only in group without family historyof atopic disease (P=0.03, OR=0.43, CI 95% 0.18;1.01).Conclusion There is a relationship between fever and atopy inchildren without family history of atopic disease.